Efeitos do manto de intemperismo sobre anomalias “VLF” dos corpos tabulares inclinados - ROZAL, Edilberto Oliveira (Universidade Federal do Pará, 2014)
Application of eletromagnetic methods for mineral exploration in tropical regions is complicated due to a presence of a conducting overburden encountered in these regions. In the Amazon region, overburden is well developed and conductive; while in semi-arid regions there may be a fine layer containing salts. Consequently, considerable error is introduced in the interpretation of EM data if the presence of the conducting overburden is ignored. In order to study the overburden effects, on VLF anomalies due inclined tabular bodies in contact with the former (Ohmic - overburden), a number of analog model experiments were conducted for varying response parameters of the overburden and the ore body. Overburden is simulated by an amonium chloride solution (NH4Cl) and the ore body by inclined grafite sheets of different thicknesses. Three overburdens of varying conductance were used to simulate diverse geological situations. Both, tilt-angle and elipsity anomalies decrease in amplitude with the increase in depth of the ore body and the position of the peak in the profile is removed further away from the crossover irrespective of the presence of the overburden or not. There is some increase and tilt-angle anomaly profiles. Eliptisity anomaly increases with the increase in the condutance of the overburden while tilt-angle anomaly decreases a little bit. However, at higher overburden condutances both of then are attenuated. Phase angle are rotated anti-clockwise with the overburden. This rotation is more intense at higher induction number of the conductor. In the presence of the ohmic-overburden and at moderate values of their condutance, the conductor appears (i) at lower depth than the real, due to the increase in the anomaly amplitude, and ii) less conducting due to the anti-clockwise rotation of the Argand diagram.